(untitled) (ფილოლოგია (სტუდენტური ჟურნალი), 2025)
The lexical unit "wonder" is of interest from a linguistic, historical, cultural, and etymological perspectives. The article explores the etymology of the word, its origin, semantic evolution, and conceptual framework. The word "wonder" originates from the Old English form "wundor", which, through linguistic transformations, gained its current morphological structure, meaning, and cultural significance. In the Georgian language, its correlate word "სასწაული" serves as an equivalent of "wonder", reflecting similar semantics. The research explores the multifaceted nature of "wonder" as an expression of human admiration, amazement, and emotional response.